Performance Of Oil Palm (Elaeis Guineensis Jacq.) Dxp Progenies From Different Agencies Under Various Planting Densities - Zainol Abidin, Mohd Isa (2007)

(untitled)
Fifteen dura x pisifera (DxP) bi-parental crosses from six Malaysian seed producers (agencies) were studied for yield, bunch quality, vegetative characters and physiological traits in four planting densities. Analysis of variance indicated significant differences among the fifteen progenies that were obtained from six agencies and planted under four planting densities. However, all the progenies and agencies were considered responding similarly across planting densities for all the 34 traits studied by showing no significant difference in genotype x planting density interaction, pooled over years. Broad-sense heritability estimates (h2B) using intra-class correlation varied between 13.3% and 47.6%. Generally, the genetic variations and heritability estimates were low, which may restrict further improvements of the parental stocks. On the other hand, uniform performance for yield is advantageous in commercial plantings. The difference in yield among progenies and among agencies reflected the different genetic background and selection pressure. The low genetic variability could be due to the narrow genetic base. The fresh fruit bunch (FFB) yield of the six agencies ranged from 18.41 to 21.46 t/ha/yr. The highest FFB yield in agency A2 was attributed to its high bunch number (BNO). Oil to bunch (O/B) varied from 25.93 to 28.21% with the latter extreme observed in agency A1. Heights (HT) of the 21-year old palms were between 8.97m and 10.02m with the height increment of between 47cm and 53cm among agencies, while the HT among densities were between 8.73m and 10.43m with the height increment of between 46cm (density D1) and 55cm (density D4). Agencies A1 and A6 had the lowest HT increment reflecting the dumpy ancestry. Oil yield (OY), which ranged from 5.11 t/ha/yr to 6.03 t/ha/yr was highest in agency A2, due its high FFB. Bunch index (BI) ranged between 0.39 and 0.43 with agency A2 was the highest. Agency A2 produced the best total economic product (TEP) at 6.93 t/ha/yr. Minimum TEP of 5.80 t/ha/yr was produced by agency A3. Density D2 (148 palms/ha) recorded the highest FFB and OY with 21.74 and 6.0 t/ha/yr, respectively. Densities D3 (170 palms/ha), D4 (215 palms/ha) and D1 (120 palms/ha) was the second, third and fourth (lowest) respectively, in FFB and OY productions. Density 2 (148 palms/ha) was the ideal planting density for maximum oil yield per unit land area. This density (148 palms/ha) is the current planting density used in commercial oil palm cultivation on inland soil.